Contribution of two native fodder trees to sheep nitrogen retention - Papachristou T.G. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
In vivo digestibility trials were conducted in metabolism cages to evaluate the contribution of immature and mature foliage of oriental hornbeam (Carpinus orientalis Mill.) and manna ash (Fraxinus ornus L.) on nitrogen retention and digestibility by sheep. Nitrogen retention did not differ (P smaller of equal than 0.5) between species (1.9 g/d for oriental hornbeam and 4.1 g/d for manna ash) in mature stage, while sheep fed with immature manna ash foliage had greater (8.6 g/d; P smaller or equal than 0.5) nitrogen retention than did those fed with the immature oriental hornbeam (5.6 g/d). Forage dry matter intakes (g/kg body weight.75) averaged 70.6 for immature and 85.8 for mature foliage and did not differ (P smaller or equal than .05) between species. Nitrogen retention followed the same pattern as dry matter digestibility, digestible nitrogen and dietary crude protein while it did not in the case of forage intake. It was concluded that foliage of both species may be an effective source of nitrogen for sheep during the long dry summer and early autumn.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)